The use of natural abundance stable isotopic ratios to indicate the presence of oxygen-containing chemical linkages between cellulose and lignin in plant cell walls - Zhou, Y.; Stuart-Williams, H.; Farquhar, G.; Hocart, C. (Pergamon, 2010)
Qualitative and quantitative understanding of the chemical linkages between the three major biochemical components (cellulose, hemicellulose and lignin) of plant cell walls is crucial to the understanding of cell wall structure. Although there is convincing evidence for chemical bonds between hemicellulose and lignin and the absence of chemical bonds between hemicellulose and cellulose, there is no conclusive evidence for the presence of covalent bonds between cellulose and lignin. This is caused by the lack of selectivity of current GC/MS-, NMR- and IR-based methods for lignin characterisation as none of these techniques directly targets the possible ester and ether linkages between lignin and cellulose. We modified the widely-accepted ‘‘standard” three-step extraction method for isolating cellulose from plants by changing the order of the steps for hemicellulose and lignin removal (solubilisation with concentrated NaOH and oxidation with acetic acid-containing NaClO2, respectively) so that cellulose and lignin could be isolated with the possible chemical bonds between them intact. These linkages were then cleaved with NaClO2 reagent in aqueous media of contrasting 18O/16O ratios. We produced cellulose with higher purity (a lower level of residual hemicellulose and no detectable lignin) than that produced by the ‘‘standard” method. Oxidative artefacts may potentially be introduced at the lignin removal stage; but testing showed this to be minimal. Cellulose samples isolated from processing plant-derived cellulose–lignin mixtures in media of contrasting 18O/16O ratios were compared to provide the first quantitative evidence for the presence of oxygen-containing ester and ether bonds between cellulose and lignin in Zea mays leaves. However, no conclusive evidence for the presence or lack of similar bonds in Araucaria cunninghamii wood was obtained.